Answer:
2x + 2(3) + 5
Explanation:
Given expression
2(x + 3) + 5
In order to solve the expressions or to simplify the expressions, basic mathematical rules are considered.
Basic mathematical rules include the BODMAS. The order is Brackets, of powers, division, multiplication, addition and then subtraction is solved at last.
For the given expression, the 2 outside the bracket (x+3) will be multiplied inside first.
=> 2(x+3) + 5
Step 1:
=> 2x + 2(3) + 5
Step 2:
=> 2x + 6 + 5
Step 3
=> 2x+11
So the first step is 2x + 2(3) + 5 ..